One Step Synthesis of Calix[n]quinones through the HClO4/PbO2‐Mediated Oxidation of Calix[n]arenes. Issue 9 (4th March 2016) - Lavendomme, Roy; Troian‐Gautier, Ludovic; Zahim, Sara; Reinaud, Olivia; Jabin, Ivan
Abstract: A procedure using HClO4 and PbO2 allows the straightforward oxidation of para ‐substituted and unsubstituted calix[ n ]arenes into the corresponding calix[ n ]quinones in approximately 82 % yield per quinone unit. These mild conditions constitute a good alternative to the classical procedure that involves highly toxic thallium(III) salts in trifluoroacetic acid. Abstract : Direct oxidation of para ‐substituted and unsubstituted calix[ n ]arenes into the corresponding calix[ n ]quinones was achieved with HClO4 and PbO2 in approximately 82 % yield per quinone unit. This method constitutes an efficient alternative to the classical procedure that involves highly toxic thallium(III) salts.